NETWORKING GAMES : network forming games and games on networks. - Mazalov, Vladimir V. (ELSEVIER ACADEMIC Press, 2019)
Networking Games: Network Forming Games and Games on Networks applies game theory methods to network analyses. Its concentration on rigorous mathematical techniques distinguishes it from other books on game theory. Developed by a mathematician and game theorist with extensive contributions to applied mathematics, game and probability theory, and written for graduate students and professionals, the book's illuminations on network games can be applied to problems in economics (in industrial organization, regulation and competition policy, for instance) and operations research.